A Case of Mosaic Down Syndrome (Bangladesh Journal of Pathology, 2009)
Cytogenetic analysis in 44 clinically suspected cases of Down syndrome (DS) was carried out using conventional Giemsa-trypsin-banding technique. Among them 43 cases were cytogenetically proved as DS. Forty-two individuals (97.7%) exhibited pure trisomy 21. The remaining child was a seven years old boy, the second-born of nonconsanguineous parents and had 46/47XY, +21 mosaicism. He also possessed most of the phenotypic characteristics of the classical trisomy 21.  Keywords: Cytogenetic analysis, Down syndrome, syndrome.   doi: 10.3329/bjpath.v24i1.2880 Bangladesh J Pathol 24 (1) : 28-30